Unified Assessment of Open and Ducted Propulsors - Rainer Schnell; Maximilian Mennicken (Aerospace)
This paper reconciles the assessment of fan and propeller performance by deriving common metrics that describe their design and operational characteristics and applies them to real-world design examples. Historically, various applications with large differences in flight Mach number and thrust requirements have led to different design methodologies and performance descriptors for ducted and unducted propulsors, making direct comparisons between these propulsion concepts challenging until today. One of the limitations of conventional propeller design methods is the difficulty in isolating the aerodynamic performance of blade sections from the overall design concept. The overall efficiency is largely impacted by top-level design parameters, while the aerodynamic quality is determined by the shaping and spanwise stacking of blade profiles. In contrast, turbomachinery design focuses primarily on the efficiency of the compression process and their respective efficiency metrics. This paper addresses these issues by systematically breaking down propeller efficiency into contributions commonly used in turbomachinery design. By applying consistent methodologies, we thereby enable a fair and quantitative comparison of the potential performance benefit of each concept. Furthermore, using common performance metrics simplifies the design process, making it more accessible to less experienced designers and facilitating the exploration of alternative design approaches for unducted propulsors.